Welfare aspects of animal transportation - Béres, Annamária; Janbaz, Janan (Animal welfare, Ethology and Housing Systems (AWETH), 2025)
The present paper reviews some of the factors that influence how an animal may react during transport. Animals can be stressed during transport by either physical stress effects (hunger, thirst, injury) or by environmental stressparameters (temperature, humidity, break up of social hierarchy etc.).Each year millions of live animals are transported across Europe. Many states introduce new regulations for animal transport that focus on animal welfare before, after and during the trips. In spite of the severe regulations, during the journey many animal welfare problems appear. With investigation the causes of these welfare problems we have possibility to improve the conditions of live transport and as a consequence of these the welfare of animals during transport can be realized.
Keywords: transport of animals; act of animal protection; animal welfare; stress factors; physiological parameters